(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Dalam praktik peralihan hak atas tanah, akta jual beli memegang peranan penting sebagai alat bukti yang otentik dan sah. Notaris sebagai pejabat umum yang diberi kewenangan oleh negara untuk membuat akta otentik berperan penting dalam menjamin kepastian hukum serta perlindungan hak-hak para pihak dalam transaksi jual beli. Artikel ini mengkaji secara yuridis normatif mengenai pelaksanaan pembuatan akta jual beli di hadapan notaris berdasarkan ketentuan dalam Undang-Undang Nomor 2 Tahun 2014 tentang Perubahan atas Undang-Undang Nomor 30 Tahun 2004 tentang Jabatan Notaris. Ditekankan pula mengenai kendala- kendala yang dihadapi notaris dalam praktik serta implikasi hukum dari akta yang dibuat. Kajian ini diharapkan dapat memberikan pemahaman komprehensif terhadap fungsi dan tanggung jawab notaris serta urgensi pembentukan akta otentik dalam setiap transaksi pertanahan. Kata Kunci: Notaris, akta jual beli, akta otentik, UU No. 2 Tahun 2014, perlindungan hukum Abstract In the practice of land rights transfer, a deed of sale and purchase plays a crucial role as an authentic and legally valid means of evidence. A notary, as a public official authorized by the state to draw up authentic deeds, holds a vital role in ensuring legal certainty and the protection of the rights of the parties involved in the transaction. This article normatively and juridically examines the implementation of the making of a deed of sale and purchase before a notary, based on the provisions of Law Number 2 of 2014 concerning the Amendment to Law Number 30 of 2004 on the Position of Notary. It also emphasizes the practical challenges faced by notaries and the legal implications of the deeds they produce. This study is expected to provide a comprehensive understanding of the notary’s functions and responsibilities, as well as the urgency of authentic deeds in every land transaction. Keywords: Notary, deed of sale and purchase, authentic deed, Law No. 2 of 2014, legal protection